Zaščita pravne osebe pred medijskimi napadi - Drevenšek, Mojca (Teorija in praksa, 1999)
Legal persons, as well as individuals, have several material and non-material (personal) rights within the latter the article especially discusses the right of honour and dignity. By reviewing the fields of Slovene criminal and civil law concerning the media attacks on organization's reputation, we also point out the possibilities of the organization's (legal) reactions to those acts. We ascert the justification of the current trend performed in some of the western democraciesČ the trend of equalizing the quality of protection from media attacks for natural and legal persons. However, there are some problems with proving the damage, especially the non-material (also called moral) damage being caused to legal persons. In case of a claim for monetary compensation (indemnity) a special condition has to be fulfilled according to the Slovene civil law the person has to suffer some physical or mental pain or fear which is impossible for the legal person. In some foreign legal systems there is a possibility to recognize the substantial diminishing of thelegal person's reputation as a (non-material) damage. The valid Slovene law is very clear about this issue the legal person can not be monetary compensated (indemnified) for the violation of its individual rights. It can only be non-monetary compensated.
Keywords: mass media; množični mediji; medijsko pravo; osebnostne pravice; varstvo pravic; odškodninska odgovornost; pravne osebe